PENGEMBANGAN KECERDASAN VERBAL BAHASA INGGRIS DI TK NEGERI GEMOLONG SRAGE - Lilis Wahyu Fatmawati (UIN Raden Mas Said Surakarta, 2022)
This paper describes the development of verbal intelligence in English at TK Negeri Gemolong Sragen. English is an international language that must be introduced to children to face global competition in the future. Therefore, this study aims to determine the teacher's strategy in stimulating the verbal intelligence of early childhood in Kindergarten Negeri Gemolong. This research method uses qualitative research methods. The results of this study indicate that the teacher's strategy in developing children's English verbal intelligence is carried out by intracurricular and extracurricular activities. Intracurricular activities are activities that are carried out based on scheduled, regular and structured activities carried out by the teacher during the learning process. In intracurricular activities the teacher uses collaborative methods from several existing methods consisting of the habituation method, the playing method, the singing method. The standard of achievement in English for children in Gemolong Kindergarten, namely self-introduction material, body parts, numbers 1-10, colors, animals, and fruit.